2019
DOI: 10.1155/2019/3201873
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Hepatic Oxidative Stress and Endoplasmic Reticulum Stress in Nonalcoholic Steatohepatitis Experimental Model

Abstract: Objective. In this study, we evaluated the efficacy of simvastatin in the treatment of nonalcoholic steatohepatitis induced by methionine and choline-deficient diet in mice and its possible effect on factors involved in the pathogenesis of the disease including oxidative stress and endoplasmic reticulum stress. Method. Male C57BL6 mice were fed either a normal diet (control) or a methionine and choline-deficient diet for four weeks and then treated orally with simvastatin (4 mg/kg once a day) for two final wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Indeed, data from large prospective randomized clinical trials suggest that atorvastatin especially ameliorates NAFLD/NASH and reduces CVS events by two fold relative to those with normal liver function [ 8 ]. Consistent with these findings, several animal studies have shown that statins attenuate NAFLD and decrease liver inflammation, steatosis, and fibrosis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Molecular studies have suggested that the mechanisms of statins’ protective activity in NASH include the activation of the adenosine monophosphate–activated protein kinase α (AMPKα) and the inhibition of c-Jun N-terminal kinases (JNK1/2), Rho kinase [ 18 ], and liver X receptor α–related genes [ 19 ].…”
Section: Introductionsupporting
confidence: 68%
“…Indeed, data from large prospective randomized clinical trials suggest that atorvastatin especially ameliorates NAFLD/NASH and reduces CVS events by two fold relative to those with normal liver function [ 8 ]. Consistent with these findings, several animal studies have shown that statins attenuate NAFLD and decrease liver inflammation, steatosis, and fibrosis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Molecular studies have suggested that the mechanisms of statins’ protective activity in NASH include the activation of the adenosine monophosphate–activated protein kinase α (AMPKα) and the inhibition of c-Jun N-terminal kinases (JNK1/2), Rho kinase [ 18 ], and liver X receptor α–related genes [ 19 ].…”
Section: Introductionsupporting
confidence: 68%
“…Notably, the present study further expanded on the mechanisms underlying such empagliflozin-induced beneficial effects on NAFLD/NASH, focusing on the gene and protein hepatic expression of factors involved in ER stress, autophagy and apoptosis which are crucial processes implicated in NAFLD development and progression [ 35 , 36 , 37 , 38 , 39 ]. Indeed, it is now well-established that under normal (unstressed) conditions, IRE1, PERK and ATF6 are inactivated upon binding to GRP78/BiP, whereas under stress conditions GRP-78/BiP dissociates from the ER stress sensors, thus activating the three arms of the UPR [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial characteristics of statins are not confined to lowering lipids and improvement of dyslipidemia. Statins also have several properties that potentiate them in the respective therapy of different disorders, including anti-inflammatory [ 74 , 75 ], antioxidant [ 76 , 77 ], neuroprotective [ 78 , 79 ], and antitumor [ 80 ]. Consumption of statins has also been related to a decreased rate of Alzheimer's disease and the development of dementia [ 81 ].…”
Section: Statinsmentioning
confidence: 99%